Pore emptying transition during nucleation in hydrophobic nanopores - Knežević, M; Yeomans, J (Royal Society of Chemistry, 2016)
Using the 2D Ising model we study the generic properties of nucleation in hydrophobic nanopores. To explore the pathways to nucleation of a spin-up phase from a metastable spin-down phase we perform umbrella sampling and transition path sampling simulations. We find that for narrow pores the nucleation occurs on the surface outside the pore. For wide pores the nucleation starts in the pore, and continues outside the filled pore. Intriguingly, we observe a pore emptying transition for a range of intermediate pore widths: a pre-critical nucleus fills the pore, continues to expand outside of the filled pore, but then suddenly gets expelled from the pore before reaching its critical size.